A Comprehensive Analysis of Online Examination Frameworks and their Applicability to Open and Distance Learning in Namibia: A Scoping Review - Amakali , Victoria Magano; Shalyefu, Rakel Kavena; Asino, Tutaleni I. (International Journal of African Higher Education, 2024)
Demand for effective assessment methods in Open and Distance Learning (ODL) is rising due to its adaptable, inclusive approach to diverse student populations. Online examination frameworks have become essential tools for ODL. This study involved a scoping review of current online examination frameworks for ODL to establish how they are implemented in higher education institutions and identify the challenges of applying them in Namibia. Data from six electronic databases for the period 2017-2022 was collected using a scoping review methodology. Of the 97 articles identified, only ten satisfied the inclusion criteria. Six relevant online examination frameworks for ODL were identified and recommendations are made to adapt these for Namibian higher education institutions offering ODL.